Employer’s civil liability for work-related accidents: a comparison of non-economic loss in Chile and England - Torres, Luis D.; Jain, Aditya Kailash (Elsevier, 2017)
Employers’ civil liability for work injuries and subsequent compensation for non-economic losses represent challenges for many countries. Several countries in Latin America and Europe still do not apply non-economic damage standards, and even when they do, the task of assessing damages is often left to a judges’ discretion. Similarly, common and civil law jurisdictions have shown non-standard ways about how these losses should be assessed and understood. This paper therefore, aims to compare England and Chile in terms of employers’ civil liability and subsequent non-economic damages compensation after work-related accidents. It focuses on the current progress made by both countries in terms of non-economic loss definition and assessment. This is a qualitative study. Research data consisted on a review of case law within the last five years in both countries. Additional, contextual data was gathered by looking at published documents examining the current English context and four interviews were carried out to further understand the Chilean context. Data was analyzed using framework analysis and the Nvivo software. From a comparative perspective, findings show that England has made important progress in terms of types of employer’s liability, understanding of non-economic loss, and standards of assessment. Although several advances have been made in Chile over the last few years, a number of challenges still remain.